Jamaica : 2009 Article IV Consultation and Request for a Stand; By Arrangement; Staff Report; Staff Supplement; Public Information Notice and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
Jamaica has been stuck in a cycle of low growth and high debt dynamics. It has been severely impacted by the global economic slowdown, and finances have deteriorated. Jamaica's objective of virtually eliminating the overall public sector deficit is appropriate. Embedding the medium-term fiscal consolidation effort in a comprehensive set of fiscal structural reforms is the key. Strengthening regulatory and supervisory frameworks along with legislative and structural reforms will reduce systemic risks to the financial system. The proposed program carries risks but these risks are manageable.